1999
DOI: 10.1159/000023429
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Expression of Progesterone Receptor Form B mRNA in Ovarian Endometriosis

Abstract: This study was designed to examine the biological implications of progesterone receptor form A (PR-A) and B (PR-B) mRNA expressions in human ovarian endometriosis (ectopic endometrium). A high ratio of PR-B to PR-AB (PR-A+PR-B) mRNA expression was found in 8 of 14 cases of endometriosis, compared with the ratio in eutopic endometrium. The mean ratio in ectopic endometria was significantly (p < 0.01) higher than in eutopic endometria. The ratio in eutopic and ectopic endometria showed no significant change duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…PR-A and PR-B differ in that the PR-B protein contains an additional sequence of amino acids at its N-terminus, which has not been detected in PR-A [20,35]. The predominance of PR-B detected in RA synovial tissue in the present study is consistent with similar findings that have recently been reported in various tissues and their disorders, including ovarian endometriosis [36], metastatic lesions of gynaecologic cancers [37], human chordomas [38] and astrocytomas grades III and IV [39]. PR-B is generally considered more efficient as a transcriptional regulator than PR-A [40,41].…”
Section: Discussionsupporting
confidence: 90%
“…PR-A and PR-B differ in that the PR-B protein contains an additional sequence of amino acids at its N-terminus, which has not been detected in PR-A [20,35]. The predominance of PR-B detected in RA synovial tissue in the present study is consistent with similar findings that have recently been reported in various tissues and their disorders, including ovarian endometriosis [36], metastatic lesions of gynaecologic cancers [37], human chordomas [38] and astrocytomas grades III and IV [39]. PR-B is generally considered more efficient as a transcriptional regulator than PR-A [40,41].…”
Section: Discussionsupporting
confidence: 90%
“…[52][53][54][55] In human gynecological cancers, especially ovarian cancers, the dominant expression of PRB mRNA is a marker for a malignant phenotype. 56 With respect to endometriosis, Misao et al 57 showed that PRB mRNA is highly expressed in endometrioma. A recent study from Wu et al 58 demonstrated how knockdown of PRB can promote cell proliferation in immortalized endometrial stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…PRA and PRB activation of gene transcription may have an important role in development of endometriosis. Since PRA dominantly acts as repressor of PRB, the ratio could be crucial (Misao et al, 1999). Unchanged PRAB expression observed in our study may thus mask differences in the PRB/PRA ratio, which may affect progesterone action in ovarian endometriomas.…”
Section: Resultsmentioning
confidence: 75%
“…The published data for the expression of ERs in endometriosis are rather contradictory. Matsuzaki et al (2001) reported no ERβ expression in 17% of ovarian endometriosis samples by TaqMan RT-PCR, while Fujimoto et al (1999) showed significantly higher expression of ERβ in ovarian endometriosis compared to normal endometrium. Recently, Bukulmez et al (2008) reported a significantly elevated ratio of ERβ/ERα mRNA in endometriomas, compared with eutopic endometrium, in agreement with our data.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation